British fascism, 1918-1939 : parties, ideology and culture - Linehan, Thomas P. (Manchester studies in modern history, 2021)
A major new and balanced study of British Fascism which surveys the development of British fascism between 1918 and 1939. Provides an accessible guide to the essential features of British fascism in the interwar period. Considers a previously under-researched area of British fascism, namely fascism and culture. Explores the various definitions of fascism, before moving on to analyse the origins of British fascism, the fascist parties and groups, fascism and culture, the membership, and British fascist antisemitism.